ANALISIS STRATEGI PROMOSI MENURUT EKONOMI ISLAM DALAM MENINGKATKAN VOLUME PENJUALAN - A. A. Miftah; Muthmainnah Muthmainnah; Amala Dinia (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
This thesis is entitled Analysis of Promotional Strategies According to Islamic Economics in Increasing Sales Volume (Study of the "Jambi Family" Electronic Store in Pematang Lumut Village, Tanjabbar). This research aims to determine promotional strategies according to Islamic economics in increasing sales volume. The method used in this research is descriptive qualitative, where in collecting data the researcher uses observation, interviews and documentation methods. The research results show that the Jambi Family Electronics Store has implemented promotions according to Islamic economics well in running its business. The obstacle in carrying out promotions according to Islamic economics is the lack of keeping promises caused by limited availability of goods which causes many consumers to have to wait and some also cancel orders because they have to wait. The second is the lack of carrying out promotional activities online. The solution in carrying out promotions is to provide availability of goods, other payments in addition to cash such as credit and being active in carrying out promotions.